PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECKS PADA POKOK BAHASAN STATISTIKA DAN PELUANG UNTUK PESERTA DIDIK KELAS VIII SMPN 25 PADANG - Meldianti . (Departemen Matematika, 2020)
Based on the results of preliminary research at grade VIII SMP in the field, most of the mathematics learning outcomes of grade VIII SMPN 25 Padang students have not been completed and students are not active during the mathematics learning process at school. One of the factors is the not optimal learning tools used by educators. From that case, to be underlying to do development learning tools of mathematics, there are plan lesson plan (RPP) and student’s worksheets (LKPD) on Pair Checks cooperative learning mode, which can provide learning experiences and have a good potential effect on student learning activities. during the learning process. Data were collected through observation, teacher interviews, and valid research sources. The subjects of this research are students grade VIII SMP. This research is a development research used plomp mode consists of phase preliminiary research, prototype phase, and assessment phase. Based on the data analysis result, it was showed that the learning equipment based on Pair Checks cooperative learning mode has fulfilled valid criteria in terms of content and construction, and has fulfilled practical criteria in terms of implementation and efficiency of time use based on student questionnaires. Keywords __ Pair Checks, development, learning devices